Topical Delivery of Emulsomal Gel for the Management of Skin Cancer - Kori, Dr. Mohan Lal (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of the present study was to develop and characterize lipid vesicular gel for managing skin cancer through topical route, because on the delivery of intact drug molecule, it distributed between normal cell and cancerous cell, leading to unacceptable side effects and also require high dose of drug to treat. Materials and Methods: Developed gel base with varying concentration of polymers and prepared emulsomes was incorporated in gel base, and then, emulsomal gel was evaluated for different parameters such as pH determination, viscosity, spreadability, homogeneity, and stability studies. The optimized emulsomal gel was done for their in vitro and in vivo drug release study. Results: The optimization of gel base was performed for different concentrations of Carbopol 934, methyl paraben sodium, glycerine, polyethylene glycol, and PVP. Emulsomal gel was prepared by distribution of emulsomes into the gel base. Physical analysis demonstrated that the resulting emulsomal gel had a light yellow color and was uniform and smooth when applied. The optimized emulsomal gel formulations were shown to be appropriate for all other characterization parameters, such as pH, viscosity, spreadability, and homogeneity. The in vitro drug release study investigation was revealed an improved emulsomal gel, showed a sustained profile over a 12 h period. Stability studies of emulsomal gel in terms of residual drug content and particle size indicated that at 25 ± 2°C temperature formulation, <2% degradation was observed over the 45 days. Skin irritation study and in vivo study were performed for developed emulsomal gel formulation. The emulsomal gel composition has been shown to be non-irritant to the skin. Hence, emulsomal gel represents promising result for improving the bioavailability of anti-cancerous drugs; moreover, emulsomal gel produces sustained drug release. Thus, the presented system explores the favorable alternative to conventional chemotherapy for the management of skin cancer through topical delivery. Conclusion: From the overall study, it was concluded that the methotrexate emulsomal gel was successfully formulated and evaluated.